Relasi Nilai Agama Islam Dan Budaya Dalam Kesenian Reog Ponorogo - Alfiati Alfiati (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
To introduce new cultural elements resulting from acculturation of Islam to Javanese culture, the Wali Songo introduced new values in a persuasive manner. Associated with sensitive issues, such as the field of trust, the guardians allowed respect for their ancestors as commonly practiced by Javanese people. For this reason, the demand to bring back Islam that is peaceful, moderate, just, and tolerant is not because of the mere longing for Nusantara Islam which is cool and reconciling, but it is already a necessity, especially since our literary values have been eroded by disturbing new understandings society. This path of cultural devices must be developed in the process of Islamization today. As Muslim scholars have explained, Islam is increasingly expected to come up with productive, constructive, and able cultural offers to declare themselves to be the bearers of goodness for all people. One of the regional arts which is a cultural heritage, Reog Ponorogo.Reog Ponorogo is one of the traditional performing arts works that has become the center of attention of the community, both locally, nationally and internationally and is one of cultural arts that has the power to become a national cultural identity. The performance is very thick with mystical things. In the art of Ponorogo Reog, there are Islamic values that are not yet known by most people today. It also shows that Islam is able to merge into the culture of Indonesian society which is one of the local wisdom. This will review the values of Islam contained in the Reog Ponorogo Arts, including the Reog section itself and the musical instruments.